Online Game Duration Associated to Neck Functional Disability in Esports Athletes - I Kadek Dwi Widhi Dharma; Ni Wayan Teza Andika; Ni Luh Anita Chandra Dewi; I.A. Pascha Paramurthi; Ida Kurniawati (Universitas Udayana dan Diaspora Taipei Medical University, 2020)
Background: Online games are a form of online recreational activity that is very easy to access and can be played at any time. Playing online games for a long time can cause several disturbances, such as a neck's functional disorder. This study aimed to determine the relationship between the duration of playing online games and Neck Functional Disability among esports. Methods: This is a cross-sectional study which was conducted in November-December 2019. The sample in this study is recruited from the esport community in Denpasar-Bali, with 62 respondents. Results: The data from 62 people, the range of active esport activity duration was 12-24 months, and the duration of active playing games per day was 5-10 hours. Most respondents aged 18-21 years were 47 respondents (75.8%), and at the age of 22-25 years were 15 respondents (24.2%). More male respondents were 42 respondents (67.7%) than 20 female respondents (32.3%). Respondents in the 13-18 months category were 28 respondents (45.2%). Category 19-24 months as many as 16 respondents (28.8%), and category 6-12 months as many as 18 respondents (29.0%). There were 24 respondents in the neck disability categories (38.7%), 18 in the severe category (29.0%), and 20 in the mild category (32.3%). Conclusion: Regardless of this study's limitations, respondents who participated actively in sports for a long period was associated with neck disabilities. Respondents who actively play online games for13-18 months and 19-24 months are associated with moderate and severe neck disabilities.